GENDER DIFFERENCE IN PERFORMANCE IN FOUR SCIENCE SUBJECTS IN BORNO STATE COLLEGES OF EDUCATION - ADAM , Mohammed; KIME, Mallam Mustapha; WALI , Hassan Mohammed (Journal of Education and Practice, 2022)
Purpose: This study examines Gender Difference in Science Subjects Performance in Borno State Colleges of Education with particular reference to Umar Ibn Ibrahim El-Kanemi College of Education, Science and Technology, Bama. The objective of the study is to find out; whether or not there exists gender difference in performance in Biology, Chemistry, Mathematics and Physics for three consecutive sessions. Methodology: Because of its suitability, the study adopted ex-post facto research design. The data for the study were collected from two independent groups (male and female) for three different sessions (2010/2011, 2011/2012 and 2012/2013). The instrument used for data collection is the Students Result Proforma designed by the researcher. Through the proforma the researcher collected the NCE 1, 2 and 3 students' CGPA. Inferential statistics (i.e. t-test) was used to analyse the data. The analysed data was presented in tables which are expressed in differences between means, variances and correlated coefficients. Stratified sampling technique was used to select gender and all the four core science subjects. All population within these departments (stratified as male and female) were utilized for the study. The t-test which was calculated at 0.05 level of significance reveals absence of differences in Chemistry and Mathematics. Findings: However, gender difference was obtained in favour of males in Biology and Physics. Unique contribution to theory, practice and policy: It was recommended that sensitization on quality science education is necessary especially in all science subjects by government and non-governmental organization to inspire female students to catch up.